2005
DOI: 10.1345/aph.1g287
|View full text |Cite
|
Sign up to set email alerts
|

The Lifestyle Challenge Program: A Multidisciplinary Approach to Weight Management

Abstract: This program is a successful multidisciplinary model for the management of overweight and obese patients in an outpatient-based hospital setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…Moreover, the employees met on a daily basis during the intervention period, and tended to share meals and have opportunities to meet immediately after work for physical exercise or other weight reduction activities [33]. The relatively low drop-out in our study compared to other studies [34,35] supports that the abovementioned factors have strengthened the completion rate in our study-group and ought to be considered in future studies and workplace initiatives for reducing excessive overweight.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, the employees met on a daily basis during the intervention period, and tended to share meals and have opportunities to meet immediately after work for physical exercise or other weight reduction activities [33]. The relatively low drop-out in our study compared to other studies [34,35] supports that the abovementioned factors have strengthened the completion rate in our study-group and ought to be considered in future studies and workplace initiatives for reducing excessive overweight.…”
Section: Discussionmentioning
confidence: 67%
“…27 However, some initiatives have demonstrated that pharmacists can successfully manage weight loss in the community and health care centers. [27][28][29] Diff erent strategies have been used by pharmacists to target weight loss including meal replacement, reduced-calorie diet or over the counter Orlistat with an average weight loss in 12 months of 1.1 to 4.1 kg. 27 We believe that the use of the plate method together with a Latin American Food Model kit in this study was a successful strategy used by the pharmacists to educate patients on portion sizes and food selections.…”
Section: Discussionmentioning
confidence: 99%
“…The National Health and Medical Research Council (Australia) [4] has recommended utilising services of various disciplines including general practitioners, dieticians, exercise physiologists, psychologists and other specialists depending on the individual's requirements. The Lifestyle Challenge Program (USA) [24] is an example of a multi-disciplinary team approach to weight management co-directed by a pharmacist and including a physician specialising in nutrition, a behavioural psychologist, a dietician and an exercise physiologist. Besides weight loss there was improvement in health-related quality of life, binge-eating behaviour and depressive symptoms.…”
Section: Collaborationmentioning
confidence: 99%